THE RELATIONSHIP BETWEEN PSYCHOLOGICAL STATES AND COGNITIVE PROCESSES IN EDUCATIONAL ACTIVITIES - Dilnavoz Xoliqova (Bright Mind Publishing, 2025)
In this article, in order to identify the factors of the quality of education of cadets, one of the main tasks of organizing a modern military educational process, the relationship of emotional states with cognitive processes in the educational process was analyzed. The article is based on the scientific research of N. D. Levitov, A. O. Prokhorov, V. A. Yakunin. In particular, experiments conducted on the basis of students' educational activities at different times were studied, and detailed conclusions were drawn on this problem.
Keywords: Military education, educational process, quality of study, objective factors, emotional states, cognitive processes, analysis of relationships, research, students' educational activities, experiment.